Placing Wild Animals in Botswana: Engaging Geography’s Transspecies Spatial Theory - Bolla, Andrea; Hovorka, Alice (Humanimalia, 2012)
This paper engages transspecies spatial theory to illuminate the dynamics of human ‘placement’ of animals and resulting human-animal encounters through a case study of wild animals in Kasane, Botswana. It details the ways in which human conceptual imaginings and material fixing of wild animals are mutually constituted and grounded in human wonderment of and economic use value associated with nonhuman animals. Resulting interspecies minglings reinforce such placements through human’s fear-based responses and ‘problem animal’ discourses, ultimately re-placing animals into spaces where-they-belong. This paper highlights specifically geographical perspectives to further explorations of human-animal relations within the realm of critical animal studies.